Opportunities for Improving Partner Notification for HIV: Results from a Community-Based Participatory Research Study. - Edelman, E Jennifer; Cole, Christopher A; Richardson, Wanda; Boshnack, Nicholas; Jenkins, Heidi; Rosenthal, Marjorie S (AIDS and behavior, 2014)
To identify actionable opportunities for improving Partner Notification (PN) for HIV among men who have sex with men (MSM), we characterized the perspectives and experiences of PN among Medical Case Managers (case managers), Disease Intervention Specialists (DIS), and MSM. In partnership with an AIDS service organization and the Connecticut State Health Department, we conducted a focus group of case managers (n = 14) and in-depth interviews with DIS (n = 7) and MSM (n = 24). We found differences between MSM's and providers' (case managers and DIS) perspectives regarding (1) determinants of sexual risk behaviors; (2) considerations impacting HIV disclosure; and (3) barriers to trusting relationships between MSM and providers. Factors impacting MSM perspectives on PN were incompletely appreciated by both case managers and DIS. PN may be improved through improving provider understanding of the complexities for MSM regarding sexual risk behaviors and disclosure and transcending barriers to trusting relationships between MSM and providers.